2009
DOI: 10.1042/bj20090061
|View full text |Cite
|
Sign up to set email alerts
|

The RhoU/Wrch1 Rho GTPase gene is a common transcriptional target of both the gp130/STAT3 and Wnt-1 pathways

Abstract: STAT3 (signal transducer and activator of transcription 3) is a transcription factor activated by cytokines, growth factors and oncogenes, whose activity is required for cell survival/proliferation of a wide variety of primary tumours and tumour cell lines. Prominent among its multiple effects on tumour cells is the stimulation of cell migration and metastasis, whose functional mechanisms are however not completely characterized. RhoU/Wrch1 (Wnt-responsive Cdc42 homologue) is an atypical Rho GTPase thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…5f, Online Resource 2). Consistent with these results, we found that E+R5020 treatment significantly increased mRNA levels of Wnt-1 and the Wnt-1-inducible gene RhoU [25] (Fig. 5g, h).…”
Section: E+ps Treatment Decreases E-cadherin Protein In Breast Cancersupporting
confidence: 78%
“…5f, Online Resource 2). Consistent with these results, we found that E+R5020 treatment significantly increased mRNA levels of Wnt-1 and the Wnt-1-inducible gene RhoU [25] (Fig. 5g, h).…”
Section: E+ps Treatment Decreases E-cadherin Protein In Breast Cancersupporting
confidence: 78%
“…Canonical Wnt signalling contributes to the regulation of Rhou in the embryo, but Rhou is not a direct transcriptional target of -catenin, and is instead probably regulated via a JNK-mediated pathway (Schiavone et al, 2009;Tao et al, 2001). The results of this and other studies on the molecular mechanism of Rhou action highlight a likely connection between Wnt signalling, epithelial morphogenesis and the formation of organ primordia via Rhoumediated changes to the cytoskeleton that affect cell shape and mechanical properties (Fig.…”
Section: Research Articlementioning
confidence: 63%
“…98 Expression of RhoU and RhoV is increased at the transcriptional level by Wnt-1; and RhoU has also been shown to be induced by STAT3 and Notch1. 47,48,99,100 The N-and C-terminal domains of RhoU and RhoV are quite different from each other. The N-terminal domain of RhoU but not RhoV contains proline-rich domains that bind to the SH3 domains of Grb2 and Nck, 101 and its C-terminal domain is phosphorylated on tyrosine 254 by Src.…”
Section: Functions and Regulation Of Atypical Rho Gtpasesmentioning
confidence: 99%